CURRENT APPLICATIONS, CLINICAL EFFICACY, AND FUTURE DIRECTIONS OF HIGH-INTENSITY FOCUSED ULTRASOUND ABLATION SURGERY IN THERAPEUTIC MEDICINE - Lian, Zhang (Tạp chí Sức khỏe và Lão hóa, 2025)
Surgical treatment has been the standard of care in selected cases with solid tumors or uterine benign diseases. However, a majority of patients are unable to undergo surgical resection because of the tumor locations, advanced stages, or poor general condition. For patients who are not suitable for surgery or unwilling to undergo surgical treatment, high-intensity focused ultrasound (HIFU) ablation surgery is a new option. HIFU is a novel non-invasive technique that can generate coagulative necrosis at a precise focal point within the body, without damaging to the surrounding structures of the target lesions, even within the path of the beam. Ultrasound guided HIFU (USgHIFU) was first used in the treatment of bone tumors in the 1990s. Over the last two decades, this technology has made significant progress and is now widely used in the treatment of various solid tumors and benign diseases of certain organs. Currently, both magnetic resonance imaging guidance focused ultrasound surgery (MRgFUS) and USgHIFU are commercially available. Each of these two types of HIFU systems has its own advantages in guidance. USgHIFU has higher treatment efficiency, with shorter treatment time, and can treat a wider range of diseases than that of MRgFUS. Recently, HIFU has been proven to be beneficial as an adjunct in the treatment of cardiovascular diseases. In addition, MRgFUS allows for non-invasive treatment of intracranial lesions is another significant advancement in the field of therapeutic ultrasound. Histotripsy was recently approved by the U.S. Food and Drug Administration (FDA) for hepatic targets. Last year, the Focused Ultrasound Foundation announced that focused ultrasound has been used for the treatment of over 170 diseases. As advances in engineering technology, including guidance techniques for the fusion of ultrasound and MRI, as well as optimization of transducer, are making HIFU treatments easier, safer, and more efficacious. This technique may play a key role in future clinical practice.